The role of a platelet Lysate-Based compartmentalized system as a carrier of cells and platelet-origin cytokines for periodontal tissue regeneration - Babo, Pedro Miguel Sousa (2016)
Currently available clinical therapies are not capable to regenerate tissues that are lost by periodontitis. Tissue engineering can be applied as a strategy to regenerate reliably the tissues and function of damaged periodontium. A prerequisite for this regeneration is the colonization of the defect with the adequate cell populations. In this study, we proposed a bilayered system composed of (1) a platelet lysate (PL)-based construct produced by crosslinking of PL proteins with genipin (gPL) for the delivery of rat periodontal ligament cells (rat-PDLCs); combined with (2) an injectable composite consisting of calcium phosphate cement incorporated with PL loaded poly(d, l-lactic-co-glycolic acid) microspheres. This system was expected to promote periodontal regeneration by the delivery of adequate progenitor cells and providing a stable system enriched with adequate cytokines and growth factors for the orchestration of tissue regrowth in periodontal defects. The bilayered system was tested in a three-wall intrabony defect in rats and the healing of periodontal tissue was assessed 6 weeks after surgery. Results showed that the bilayered system was able to promote the regrowth of functional periodontal tissues, both with (cells + gPL) and without the loading of PDLCs (gPL). Significant connective tissue attachment (45.0 â 15.0% and 64.0 â 15.0% for gPL and cells + gPL group, respectively) and new bone area (33.8 â 21% and 21.3 â 3% for gPL and cells + gPL group, respectively) were observed. Nevertheless, rat PDLCs delivered with gPL construct in the defect area were hardly visible 6 weeks after surgery and did not contribute for the regeneration of new periodontal tissue. Overall, our findings show that the bilayered system promotes the stabilization of PL proteins on the root surface and has a positive effect in the repair of periodontal tissues both in quality and in quantity.